Habits, Triggers and Moral Formation - Knobel, Angela (Studies in Christian ethics, 2023)
This article examines moral change, primarily through the lens of Summa Theologiae I-II 49–50. I argue that the specific difference Aquinas asserts between habits and dispositions allows for the possibility that virtuous habits can sometimes exist alongside problematic bodily dispositions. While in the typical case the actions that bring about a habit also bring about appropriate bodily dispositions, it is my contention that the cultivation of a habit need not eliminate all contrary bodily dispositions. This implies that one's past, whether it be one's pre-rational conditioning or past choices, can create bodily obstacles to the cultivation of virtue that later moral reformation may never entirely eliminate.